2017
DOI: 10.1080/14737159.2017.1340833
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a hormonal and metabolic disorder affecting 5 to 20% of reproductive-aged women worldwide that results in androgen excess, menstrual dysfunction and oligo-ovulatory subfertility, with increased risks for type 2 diabetes, endometrial adenocarcinoma, and potentially vascular disease, among other morbidities. PCOS is a complex genetic trait with strong heritability accounting for as high as 70% of the development of the disorder. Areas covered: The authors summarize the histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 87 publications
1
38
0
6
Order By: Relevance
“…PCOS is a uniquely challenging, multi-faceted disorder in which progressive obesity enhances severity of phenotype while diminishing wellbeing and quality of life [22]. The findings that hyperandrogenism and metabolic dysfunction cluster in PCOS families [23,24] are consistent with genetic susceptibility. Other causes of hyperandrogenism may also contribute to the development or aggravation of PCOS, including LH hypersecretion, adipogenic constraint and obesity leading to compensatory hyperinsulinemia arising from insulin resistance, as well as fetal androgen exposure [3,25,26].…”
Section: Pcos and Its Potential Originsmentioning
confidence: 81%
“…PCOS is a uniquely challenging, multi-faceted disorder in which progressive obesity enhances severity of phenotype while diminishing wellbeing and quality of life [22]. The findings that hyperandrogenism and metabolic dysfunction cluster in PCOS families [23,24] are consistent with genetic susceptibility. Other causes of hyperandrogenism may also contribute to the development or aggravation of PCOS, including LH hypersecretion, adipogenic constraint and obesity leading to compensatory hyperinsulinemia arising from insulin resistance, as well as fetal androgen exposure [3,25,26].…”
Section: Pcos and Its Potential Originsmentioning
confidence: 81%
“…Studies involving more than 100 candidate genes, especially those related to reproductive axis, insulin resistance and chronic inflammation have not shown reproducible results (38,39). The lack of consistency across studies may stem from the small sample size, phenotypic heterogeneity among patients, an inadequate control group, the lack of comorbidity matching (obesity, insulin resistance), or the limitation to only one or two variants genotyped in each gene of interest instead of the whole gene (40).…”
Section: Pcos Genetic Heritabilitymentioning
confidence: 99%
“…The ovary is not the only affected tissue in the disease, as women with PCOS also exhibit adipose tissue dysfunction (Cortón et al 2007, Thessaloniki ESHRE/ASRM-Sponsored PCOS Consensus Workshop Group 2008, insulin resistance in the skeletal muscle (Silva Dantas et al 2013), elevated serum levels of inflammatory markers (Orio et al 2005, Diamanti-Kandarakis et al 2006a, Escobar-Morreale et al 2011 and endometrial alterations (Piltonen 2016). Several studies have demonstrated the impact of genetic and environmental factors on the PCOS etiology (Abbott et al 2005, Diamanti-Kandarakis et al 2006b, Azziz et al 2016, Mykhalchenko et al 2017. Lately, epigenetic factors have garnered considerable attention in the study of the PCOS pathogenesis, considering that intrauterine and environmental insults, as well as lifestyle factors, might predispose to the disease development (Escobar-Morreale 2018b, Patel 2018, Smyka et al 2018, Tata et al 2018.…”
Section: Introductionmentioning
confidence: 99%